Sketch-based Interfaces and Modeling - Jorge, Joaquim; Samavati, Faramarz; SpringerLink (Online service). (London Springer London Imprint: Springer, 2011)
The field of sketch-based interfaces and modeling (SBIM) focuses on developing methods and techniques to enable users to interact with a computer through sketching - a simple, yet highly expressive medium. SBIM blends concepts from computer graphics, human-computer interaction, artificial intelligence, and machine learning. Recent improvements in hardware, coupled with new machine learning techniques for more accurate recognition, and more robust depth inferencing techniques for sketch-based modeling, have resulted in an explosion of both sketch-based interfaces and pen-based computing devices. Presenting the first coherent, unified overview of SBIM, this unique text/reference bridges the two complementary research areas of user interaction (sketch-based interfaces), and graphical modeling and construction (sketch-based modeling). The book discusses the state of the art of this rapidly evolving field, with contributions from an international selection of experts. Also covered are sketch-based systems that allow the user to manipulate and edit existing data - from text, images, 3D shapes, and video - as opposed to modeling from scratch. Topics and features: Reviews pen/stylus interfaces to graphical applications that avoid reliance on user interface modes Describes systems for diagrammatic sketch recognition, mathematical sketching, and sketch-based retrieval of vector drawings Examines pen-based user interfaces for engineering and educational applications Presents a set of techniques for sketch recognition that rely strictly on spatial information Introduces the Teddy system; a pioneering sketching interface for designing free-form 3D models Investigates a range of advanced sketch-based systems for modeling and designing 3D objects, including complex contours, clothing, and hair-styles Explores methods for modeling from just a single sketch or using only a few strokes This text is an essential resource for researchers, practitioners and graduate students involved in human-factors and user interfaces, interactive computer graphics, and intelligent user interfaces and AI. Dr. Joaquim Jorge is a professor at the Computer Science and Engineering Department (DEI) of the School of Engineering (IST) at the Technical University of Lisbon, Portugal. Dr. Faramarz Samavati is an associate professor at the Department of Computer Science at the University of Calgary, Canada.
Part I: Sketch-Based Interfaces -- Minimizing Modes for Smart Selection in Sketching/Drawing Interfaces -- Multi-domain Hierarchical Free-sketch Recognition using Graphical Models -- Mathematical Sketching: An Approach to Making Dynamic Illustrations -- Pen-based Interfaces for Engineering and Education -- Flexible Parts-based Sketch Recognition -- Sketch-Based Retrieval of Vector Drawings -- Part II: Sketch-Based Modeling -- A Sketching Interface for Freeform 3D Modeling -- The Creation and Modification of 3D Models using Sketches and Curves -- Sketch-Based Modeling and Assembling with Few Strokes -- ShapeShop: Freeform 3D Design with Implicit Solid Modeling -- Inferring 3D Freeform Shapes from Complex Contour Drawings -- The Creation and Modification of 3D Models using Sketches and Curves -- Dressing and Hair-styling Virtual Characters from a Sketch.
Electronic reproduction.
Keywords: User interfaces (Computer systems).; Model-integrated computing; Computer simulation; Electonic book